EFEKTIVITAS KEBIJAKAN PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (SUATU STUDI DI KECAMATAN KAWANGKOAN UTARA) - Wonok, Yolanda; Tulusan, Femmy; Ruru, Joorie (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT:Empowerment of small and medium micro enterprises is one of the policies made by theIndonesian government in improving the welfare of society. and in accordance with law no.20 of 2008regulates micro, small and medium-sized businesses, as well as by government regulation no. 13 of 2013 onthe implementation of law No. 20 of 2008, the government made a policy regarding the development programsof small and medium micro enterprises.Policy pursued by the government in improving the empowerment of micro, small and medium enterprises arethe government gave permission for business in running a certain business activities; business developmentthrough the provision of facilities, coaching and mentoring; assistance to foster and improve the capabilitiesand competitiveness of businesses; coordination and control of the government. Small and medium micropolicies have also been imposed by the government in the district of northern Kawangkoan.Problems to be answered in this research is how the effectiveness of the empowerment of small and mediummicro enterprises in Kawangkoan northern districts. This study used qualitative methods, this study aimed todescribe, analyze and determine the effectiveness of the empowerment policy of small and medium microenterprises. Results of research conducted by collecting data obtained through observation and interviewsbased on several indicators, as follows: (1) Responsiveness, (2) Development, (3) Adequacy.Based on the results of the study conclude that the policy of empowerment of micro, small and medium-sizedenterprises in the district north Kawangkoan already quite effective. Based on the conclusion of the study, it issuggested to Kawangkoan northern district government to pay more attention to the needs of the microbusiness small and medium in increasing empowerment of small and medium micro enterprises.Key words: effectiveness, policy, empowerment.